Prognostic Value of Sarcopenia in Patients With Diffuse Large B-Cell Lymphoma Treated With R-CHOP: A Systematic Review and Meta-Analysis - Xu, Xin-Tian; He, Dong-Liang; Tian, Meng-Xing; Wu, Hui-Jing; Jin, Xin (Frontiers in Nutrition, 2022)
Objective: Several studies have reported conflicting results regarding the association between sarcopenia and outcomes in patients with diffuse large B-cell lymphoma (DLBCL). This meta-analysis aimed to evaluate the prognostic value of sarcopenia in patients with DLBCL. Methods: PubMed, Embase, and Cochrane Library databases were searched to identify trials exploring the association between sarcopenia and prognosis in patients with DLBCL treated with chemotherapy. A meta-analysis of overall survival (OS), progression-free survival (PFS), treatment completion, and rate of complete response (CR) was performed. Results: Twelve studies that involved 2324 patients with DLBCL were included. Sarcopenia was associated with poor OS and PFS in patients with DLBCL, even after adjusting for confounders. Patients with sarcopenia had lower rates of CR and treatment completion than patients without sarcopenia. Conclusions: Sarcopenia is a negative predictor of prognosis in patients with DLBCL. Additional and prospective studies investigating the diagnostic criteria for sarcopenia are warranted.